2007
DOI: 10.1073/pnas.0608779104
|View full text |Cite
|
Sign up to set email alerts
|

Indirect activation of a plant nucleotide binding site–leucine-rich repeat protein by a bacterial protease

Abstract: Nucleotide binding site-leucine-rich repeat (NBS-LRR) proteins mediate pathogen recognition in both mammals and plants. The molecular mechanisms by which pathogen molecules activate NBS-LRR proteins are poorly understood. Here we show that RPS5, a NBS-LRR protein from Arabidopsis, is activated by AvrPphB, a bacterial protease, via an indirect mechanism. When transiently expressed in Nicotiana benthamiana leaves, full-length RPS5 protein triggered programmed cell death, but only when coexpressed with AvrPphB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
414
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(428 citation statements)
references
References 44 publications
8
414
2
4
Order By: Relevance
“…From these data, a picture emerges in which the LRR domain is not only involved in pathogen recognition, but also plays a role in maintaining an autoinhibited resting state in the absence of pathogens via its interactions with the other domains (Bendahmane et al, 2002;Hwang and Williamson, 2003;Ade et al, 2007;Qi et al, 2012). A similar role as regulatory domain has been found for the sensor domains of other NLRs, such as the mammalian Apaf1 (Hu et al, 1998).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…From these data, a picture emerges in which the LRR domain is not only involved in pathogen recognition, but also plays a role in maintaining an autoinhibited resting state in the absence of pathogens via its interactions with the other domains (Bendahmane et al, 2002;Hwang and Williamson, 2003;Ade et al, 2007;Qi et al, 2012). A similar role as regulatory domain has been found for the sensor domains of other NLRs, such as the mammalian Apaf1 (Hu et al, 1998).…”
mentioning
confidence: 75%
“…Previous studies have shown that the CC/TIR, NB-ARC, and LRR domains in plant immune receptors interact and cooperate with each other in an interdependent manner Leister et al, 2005;Ade et al, 2007;Rairdan et al, 2008). From these data, a picture emerges in which the LRR domain is not only involved in pathogen recognition, but also plays a role in maintaining an autoinhibited resting state in the absence of pathogens via its interactions with the other domains (Bendahmane et al, 2002;Hwang and Williamson, 2003;Ade et al, 2007;Qi et al, 2012).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…PBS1 is cleaved by an effector of the pathogen Pseudomonas syringae, activating the nucleotidebinding site (NB)-LRR protein, RPS5, which triggers programmed cell death (Warren et al, 1999;Swiderski and Innes, 2001;Shao et al, 2003;Ade et al, 2007). A recent study has revealed that, like PBS1, BIK1 and several PBS1-like (PBL) RLCKs are also substrates of the bacterial AvrPphB protease effector .…”
mentioning
confidence: 99%
“…Although receptor-like cytoplasmic kinases (RLCKs) account for at least 125 of the 610 annotated RLKs in Arabidopsis (Arabidopsis thaliana), much remains to be learned about their functions within cell signaling complexes (Shiu and Bleecker, 2001;Goring and Walker, 2004;Shiu et al, 2004;Jurca et al, 2008). Several of the 46 RLCKs assigned to the class VII subfamily have been found to function in pathogen response and developmental signaling pathways (Swiderski and Innes, 2001;Shao et al, 2003;Murase et al, 2004;Muto et al, 2004;Veronese et al, 2006;Ade et al, 2007;Lu et al, 2010;Zhang et al, 2010;Liu et al, 2011).…”
mentioning
confidence: 99%